Strengthening the Position of the Honored Council of Election Organizers (DKPP) in the Indonesian State System Analysis of the Effectiveness of Enforcement of the 2024 Post-Election Organizer Code of Ethics Study: Normative - Rohmawati Berutu; Janpatar Simamora; Hisar Siregar (Journal of Law, Politic and Humanities, 2025)
This research examines the strengthening of the position of the Honorary Council of Election Organisers (DKPP) in the Indonesian constitutional system, focusing on the enforcement of the code of ethics after the 2024 elections. Through normative research methods and literature studies, the research found that DKPP has worked quite effectively so far and needs to be developed and maintained. DKPP has proven to be an independent institution with final and binding decisions, having an equal position with the KPU and Bawaslu in the system of checks and balances. The study reveals the urgency of transforming DKPP into an Election Court, which requires the 5th amendment of the 1945 Constitution to include DKPP in the judicial power according to article 24. Despite facing institutional, regulatory and operational challenges, the study concludes that strengthening DKPP requires a comprehensive approach and multi-stakeholder support to realise more effective and sustainable code of ethics enforcement in the Indonesian constitutional system.Keywords: DKPP, Election Code of Ethics,Constitutional System, Election Court, Election Organiser, 1945 Constitutional Amendmentio.